2022
DOI: 10.3390/metabo12070650
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling of Rheumatoid Arthritis Neutrophils Reveals Altered Energy Metabolism That Is Not Affected by JAK Inhibition

Abstract: Neutrophils play a key role in the pathophysiology of rheumatoid arthritis (RA) where release of ROS and proteases directly causes damage to joints and tissues. Neutrophil function can be modulated by Janus Kinase (JAK) inhibitor drugs, including tofacitinib and baricitinib, which are clinically effective treatments for RA. However, clinical trials have reported increased infection rates and transient neutropenia during therapy. The subtle differences in the mode of action, efficacy and safety of JAK inhibitor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…In our previous study we identified that the metabolome in RA neutrophils is different from HC, mainly driven by metabolites of central carbon metabolism (glucose, ATP, NADP, lactate) [18]. In this study we wanted to further investigate the reasons for this, and therefore we first analysed the expression of genes regulating glycolysis in RA neutrophils.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous study we identified that the metabolome in RA neutrophils is different from HC, mainly driven by metabolites of central carbon metabolism (glucose, ATP, NADP, lactate) [18]. In this study we wanted to further investigate the reasons for this, and therefore we first analysed the expression of genes regulating glycolysis in RA neutrophils.…”
Section: Resultsmentioning
confidence: 99%
“…In this study we investigated HC and RA neutrophil responses when challenged with inhibitors of central carbon metabolism or low extracellular glucose concentrations. Recent studies have highlighted the importance of pathways connected to glycolysis in neutrophils, including glycogenolysis, gluconeogenesis, glutaminolysis and PPP [17, 18] and this work provides new information about the critical role of glucose metabolism in human neutrophils.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ozanimod is FDA‐approved for moderately to severely active UC [ 8 ]. Tofacitinib is FDA‐approved for the treatment of RA, UC, and psoriatic arthritis [ 2 , 7 , 10 ]. Multiple clinical trials have investigated neutrophil‐targeting agents, including tofacitinib, in the context of several diseases and have found that treatment side effects exist [ 2 , 7 , 8 ].…”
mentioning
confidence: 99%